KONSEP UMUM PENELITIAN KUALITATIF PADA RANAH PENDIDIKAN - Putra, Eka Mahendra (As-Sulthan Journal of Education, 2025)
This study discusses the basic concepts of qualitative research in education. Qualitative research is a process of understanding human or social phenomena by creating a comprehensive and complex picture. The main purpose of qualitative research is to understand a phenomenon that occurs or a social phenomenon by focusing research on a complete picture of the social phenomenon being studied. Qualitative research has several methods, including phenomenology, ethnography, and case studies. Data collection techniques in qualitative research can be done through observation, interviews, and documentation. Data analysis in qualitative research can be done through the Miles and Huberman technique, as well as the Spradley technique. This study aims to provide a clearer picture of the basic concepts of qualitative research in education. Thus, this study is expected to contribute to the development of qualitative research in education and improve the quality of research in the future. It can also help raise awareness of the importance of qualitative research in education. With this hope, this study can be a reference.